Research on the applicability of high-precision underground exploration technology to public roads in Bangkok: Part 1 – Trend analysis of detected cavities - Yamashina, Mitsumasa; Kongkikool, Warach; Shinohara, Jun; Kinoshita, Naoki (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 30, 2025)
This study demonstrates the effectiveness of Ground Penetrating Radar Mobile Mapping System 3D (GMS3) technology in detecting subsurface cavities across various public road classifications in Thailand. A total survey length of 338 km identified 313 potential cavities, with comparable detection rates of 0.92, 0.94, and 0.93 cavities per lane (km) for urban main roads, urban sub-roads (Soi), and suburban main roads, respectively. Notably, the first lane of urban main roads showed a higher detection rate (1.21), over twice that of internal lanes (0.57), while suburban main roads exhibited a fivefold difference (2.12 vs. 0.04). Analysis of Bangkok’s three generational zones revealed the lowest detection rate in Gen.3 (0.50), closely aligned with Japan’s main road rate (0.44). Variations are attributed to infrastructural density and historical pavement quality. The GMS3 system effectively visualizes subsurface features up to 1.5 m deep, supporting its application in proactive and data-driven road asset management. These findings advocate for the use of cavity heat maps to inform infrastructure maintenance strategies.